Regulation of Interferon Gamma Signaling by Suppressors of Cytokine Signaling and Regulatory T Cells - Larkin, Joseph; Ahmed, Chulbul M.; Wilson, Tenisha D.; Johnson, Howard M. (Frontiers in Immunology, 2013)
Regulatory T cells (Tregs) play an indispensable role in the prevention of autoimmune disease, as interferon gamma (IFN) mediated, lethal autoimmunity occurs (in both mice and humans) in their absence. In addition, regulatory T cells have been implicated in preventing the onset of autoimmune and auto-inflammatory conditions associated with aberrant IFN signaling such as type 1 diabetes, lupus, and LPS mediated endotoxemia. Notably, suppressor of cytokine signaling 1 deficient (SOCS1-/-) mice also succumb to a lethal auto-inflammatory disease, dominated by excessive IFN signaling and bearing similar disease course kinetics to Treg deficient mice. Moreover SOCS1 deficiency has been implicated in lupus progression, and increased susceptibility to LPS mediated endotoxemia. Although it has been established that Tregs and SOCS1 play a critical role in the regulation of IFN signaling, and the prevention of lethal auto-inflammatory disease, the role of Treg/SOCS1 cross-talk in the regulation of IFN signaling has been essentially unexplored. This is especially pertinent as recent publications have implicated a role of SOCS1 in the stability of peripheral Tregs. This review will examine the emerging research findings implicating a critical role of the intersection of the SOCS1 and Treg regulatory pathways in the control of IFN gamma signaling and immune system function.